Critical Literacy Practice for EFL Reading Classroom - Mas Pupah, Emmas (Journal of Literature Language and Academic Studies, 2023)
Critical literacy becomes increasingly known in the EFL context because it plays a significant role in encouraging the learners to think critically about the linguistic hierarchy, to be aware of cultural domination, and to develop their voice in social justice within the target language. Despite this, many EFL teachers and teachers-educators are still unfamiliar with how it is enacted. The abstract tenets of critical theory and the nature of critical practice cause this unfamiliarity. In this paper, the researchers elaborate on some books, articles, and previous research to assist the teachers in understanding the complexity of critical literacy practice and to propose the appropriate practical steps for implementing critical literacy. The teachers can follow these practical steps in their EFL reading classroom. First, appropriate teaching materials are reviewed. Second, the teaching strategy to implement critical literacy is discussed. Third, practical ways of applying critical literacy are proposed in this practical framework.